Living Life Through Sport: The Transition of Elite Spanish Student-Athletes to a University Degree in Physical Activity and Sports Sciences - Mateu, Pau; Inglés, Eduard; Torregrossa, Miquel; Marques, Renato Francisco Rodrigues; Stambulova, Natalia; Vilanova, Anna (Frontiers in Psychology, 2020)
Interest in studying the different transitions faced by elite athletes throughout their careers has grown significantly in recent years. While transition from secondary school to university is an important research area in Europe, there is a void of studies on how student-athletes experience the transition to specific degrees. One of the most sought-after university degrees among elite athletes in Spain is a degree in Physical Activity and Sport Sciences (PASS). The first aim of this study was to investigate the main demands, barriers, and resources perceived by elite student-athletes in various phases of dual career transition to a university degree in PASS. The second aim was to identify the transition pathways pursued depending on the subjective importance they attached to sport and education. Eleven elite student-athletes (Mage = 20.7, SD = 1.6 years) who were in their second and third year of the degree in PASS participated in semi-structured interviews. Deductive-inductive thematic analysis of the interview transcripts revealed three main themes: (a) general university transition issues, (b) PASS-specific transition issues, and (c) transition pathways. Our results show that the close link between sport and the content of the degree was perceived by the elite student-athletes as their main resource. This link, however, was also perceived as a major barrier as the compulsory practical subjects entailed a risk of injury or overtraining that could affect both athletic and academic development. We noticed how the importance they attached to sport or studies varied at different moments of the transition period, a phenomenon we termed "fluid transition pathways". Dual career promotion for elite athletes is an important part of European sports policy and our findings provide new knowledge that could help Spanish PASS faculties develop specific assistance programs to support transitioning student-athletes.